Pediatric home mechanical ventilation: A Canadian Thoracic Society clinical practice guideline executive summary. Issue 1 (2nd January 2017) - Amin, Reshma; MacLusky, Ian; Zielinski, David; Adderley, Robert; Carnevale, Franco; Chiang, Jackie; Côté, Aurore; Daniels, Cathy; Daigneault, Patrick; Harrison, Christine; Katz, Sherri; Keilty, Krista; et al.
ABSTRACT: Over the last 30 to 40 years, improvements in technology, as well as changing clinical practice regarding the appropriateness of long-term ventilation in patients with "non-curable" disorders, have resulted in increasing numbers of children surviving what were previously considered fatal conditions. This has come but at the expense of requiring ongoing, long-term prolonged mechanical ventilation (both invasive and noninvasive). Although there are many publications pertaining to specific aspects of home mechanical ventilation (HMV) in children, there are few comprehensive guidelines that bring together all of the current literature. In 2011 the Canadian Thoracic Society HMV Guideline Committee published a review of the available English literature on topics related to HMV in adults, and completed a detailed guideline that will help standardize and improve the assessment and management of individuals requiring noninvasive or invasive HMV. This current document is intended to be a companion to the 2011 guidelines, concentrating on the issues that are either unique to children on HMV (individuals under 18 years of age), or where common pediatric practice diverges significantly from that employed in adults on long-term home ventilation. As with the adult guidelines, 1 this document provides a disease-specific review of illnesses associated with the necessity for long-term ventilation in children, including children with chronic lung disease, spinal muscle atrophy, muscular dystrophies, kyphoscoliosis, obesity hypoventilation syndrome, and central hypoventilation syndromes. It also covers important common themes such as airway clearance, the ethics of initiation of long-term ventilation in individuals unable to give consent, the process of transition to home and to adult centers, and the impact, both financial, as well as social, that this may have on the child's families and caregivers. The guidelines have been extensively reviewed by international experts, allied health professionals and target audiences. They will be updated on a regular basis to incorporate any new information.